Drug use in rural China: a preliminary investigation in Hunan Province. - Deng, Qijian; Tang, Quansheng; Schottenfeld, Richard S; Hao, Wei; Chawarski, Marek C (Addiction (Abingdon, England), 2012)
To compare characteristics and illicit drug abuse patterns among drug abusers in rural and urban areas of Hunan Province, China. MEASUREMENTS AND DESIGN: Data collected by public security bureau on newly registered drug abusers between 2005 and 2008 in five urban and five rural areas (n = 1639) were extracted anonymously and analyzed.
Keywords: Adolescent; Adult; China; Female; Humans; Male; Middle Aged; Needle Sharing; Prevalence; Registries; Rural Population; Street Drugs; Substance-Related Disorders; Urban Population; Young Adult